Analysis of the forming process of conical-like helical surfaces with roller tools - Kacalak, Wojciech; Budniak, Zbigniew; Szafraniec, Filip (Zielona Góra: Uniwersytet Zielonogórski)
The article presents a methodology of an analysis and modeling of technological systems and the grinding process of conical-like helical surfaces with the use of modern CAD/CAE systems and calculations in the Matlab system. The methodology developed allows one to carry out simulation tests for the accuracy of the grinding process of helical surfaces taking into consideration the deviations of the location and shape of the system`s elements, axial and radial striking the spindle of the workpiece machined and the grinding wheel as well as the tool`s geometrical features.
Keywords: grinding; CAD/CAE; axial profile; helical surface; Matlab